A case study: the readiness of Perpustakaan Tun Abdul razak in positioning towards digital library / Mohd Azmirul Khair Mohd Yusuf - Mohd Yusuf, Mohd Azmirul Khair (Faculty of Information Management, 2008)
This research that been conducted to know the perception of library user on the Perpustakaan Tun Abdul Razak Puncak Perdana services and facilities and the readiness of the Perpustakaan Tun Abdul Razak Puncak Perdana in positioning towards digital library environment that focusing on the student from UiTM Puncak Perdana. There is three aspect that been discuss in this research that is the student perception on the digital library services and facilities provided by PTAR Puncak Perdana, the awareness of student in the UiTM Puncak Perdana on the digital library scenario and lastly focusing on the PTAR Puncak Perdana itself, that is about the skills and competencies needed for library staff towards positioning to digital library. 100 respondents has been choose randomly from three faculty in UiTM Puncak Perdana that is 40 respondents from Faculty of Information management, 30 respondents from Faculty of Mass Communication and 30 respondents from Faculty of Technology Creative and Artistic. From the survey we can conclude that among three faculties in the UiTM puncak Perdana, students from Faculty of Technology Creative and Artistic is the lowest user of PTAR's digital library and Student from Faculty of Information Management is the highest user of PTAR's digital library.